Performance of chlorothalonil levels and spraying intervals on Asian rust control and soybean grain yield - Reis,Erlei Melo (2019)
ABSTRACT In an experiment conducted in the field, during the 2017/18 growing season, with the soybean cultivar Syn 1561 IPRO, the interaction of chlorothalonil levels with application intervals was evaluated for the control of Asian soybean rust, caused by Phakopsora pachyrhizi. The first fungicide application was performed in V8 stage, 44 days after emergence, with 1.85% rust leaflet incidence. The experiment consisted of a factorial arrangement with five fungicide levels (1.0, 1.5, 2.0, 2.5 and 3.0 L/ha) applied at 8, 12 and 16-day intervals, using randomized block treatments and four replicates. A self-propelled sprayer with 16 bars, XR11001VS nozzles and 150 L/ha volume was employed. Leaflet rust severity in R5.4 stage and grain yield were evaluated. Data were subjected to analysis of variance, and means were compared according to Tukey’s test. At eight-day intervals (six sprayings), control ranged from 75% to 93%; at 12-day intervals (four sprayings), it ranged from 35 to 63%, and at 16-day intervals (three sprayings), control ranged from 15 to 29% according to the sprayed levels. The longer the interval between applications, the lower the response of the used level for rust control and soybean grain yield. Chlorothalonil showed fungitoxicity to integrate a program of anti-resistance strategies to control soybean rust.